Estudio de factibilidad para la creación de un centro comercial para la reubicación del sector informal del centro, cantón El Empalme, año 2015 - Aspiazu García, Cynthia Alejandra (2015)
This project feasibility, It provides perform a market study on the current situation of informal traders, analyzing the different factors that make up the same, the creation of the shopping center "El Empalme", will give informal traders stability, organization and better income, since they are located in a place free from all kinds of problems, as times of rains among other influential factors in the work of these traders. It should be emphasized that the creation of this mall will give a better image to Canton, since all traders engaged in the marketing of clothing, footwear and bazaar items, will be relocated and this will help you have better traffic flow, clean streets and organization within the Canton. It shows the contextual framework of the research and the introduction raises the issue under study. Through a market survey in the Canton El Empalme, 2015, the investigation found that there is 78% of customers who purchased the clothing, footwear and bazaar items in different positions informal traders, however customers are not satisfied in full by the way how these informal traders are located, and different problems like dirt in the streets, disorganization and bad image for the Canton that the same originate. The shopping center will feature 143 shops built in a single size for all traders, thus achieving that there is any discord, since all local will be the same size, will also have toilets located inside the mall, as well as a manager, two assistant cleanings and two guards to assist in the work being carried out inside the mall "El Empalme". This project will have an investment of $ 488,014.25, estimating get the return on investment over a period of five years, the final cost of each shop will be $ 5000, distributed in 60 installments of $ 83.33 that will amount to pay monthly for each trader. This project has an IRR of 47%, which ensures the viability of the project.